APPLICATIONS OF PHOTOMODELER IN PORT AU PRINCE, HAITI - Ridho Prawiro; Regan Potangaroa; Happy Ratna Santosa (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2012)
Innovation and technology is increasingly considered the bedrock of an innovative and smart society and its consequent settlement. Habitat II, held in Istanbul, Turkey in 1996, endorsed important changes in the approach to human settlements, acknowledging the need for guiding urbanization, rather than preventing it. In all 171 governments adopted the agenda and the need to equitably spread the benefits of economic growth, and to fulfill basic housing and employment requirements. Translating these goals into quantitative, measurable targets has seemingly been problematic for engineers and architects and moreover, the application of tech-nology as part of any innovative and smart settlement has been elusive. This paper looks at application of one innovative technology that has only developed recently using photographs to produce 3D drawings of the photographed area. It looks at several areas of application in post disaster reconstruction in Port au Prince Haiti from the January 12 2010 earthquake. While the method is not especially site specific, its application in such a devastated context would suggest portability to other settlement disaster and non disaster in both. The key conclusion from this design based research is the need for quality as an integral part of any post disaster reconstruction program but also as part of any sustainable, innovative smart settlement.